A fashion retailer's guide to thriving in turbulent times - Boustani, Ghalia; Leonini, Daniela (New York, NY : Routledge, 2023)
"By raising questions and providing scenarios for success, this book embraces fashion brand development in current turbulent retail environments. A brand must have an essence, a heart; it needs to respect a philosophy or abide by values. A brand's success and sustainability follow specific rules, nonetheless for fashion brands. But do fashion brand identity rules apply in today's turbulent times? Acknowledging and going beyond branding theory, this book challenges knowledge and practices that have been guiding fashion retail brands for many years. Co-written by a Sorbonne researcher and a retail consultant with 30 years' experience, this practical guide offers not a process that fashion brands must follow, but potential avenues for survival in today's retail market and facing today's customers. Professionals in and students of fashion retailing and branding will appreciate the detailed case studies that illustrate main concepts, and thought-provoking suggestions of how to make decisions for an uncertain future"--
Keywords: Fashion merchandising; Branding (Marketing); BUSINESS & ECONOMICS / Industries / Retailing; BUSINESS & ECONOMICS / Industries / Textile Industry; BUSINESS & ECONOMICS / Marketing / Direct